Repurposing Anti-Malaria Phytomedicine Artemisinin as a COVID-19 Drug - Uckun, Fatih M.; Saund, Saran; Windlass, Hitesh; Trieu, Vuong (Frontiers in Pharmacology, 2021)
Artemisinin is an anti-inflammatory phytomedicine with broad-spectrum antiviral activity. Artemisinin and its antimalarial properties were discovered by the Chinese scientist Tu Youyu, who became one of the laureates of the 2015 Nobel Prize in Physiology or Medicine for this breakthrough in tropical medicine. It is a commonly used anti-malaria drug. Artemisinin has recently been repurposed as a potential COVID-19 drug. Its documented anti-SARS-CoV-2 activity has been attributed to its ability to inhibit spike-protein mediated and TGF-b-dependent early steps in the infection process as well as its ability to disrupt the post-entry intracellular events of the SARS-CoV-2 infection cycle required for viral replication. In addition, Artemisinin has anti-inflammatory activity and reduces the systemic levels of inflammatory cytokines that contribute to cytokine storm and inflammatory organ injury in high-risk COVID-19 patients. We postulate that Artemisinin may prevent the worsening of the health condition of patients with mild-moderate COVID-19 when administered early in the course of their disease.